2015
DOI: 10.1097/md.0000000000002030
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Role of MicroRNAs in Psoriasis

Abstract: Psoriasis is recently characterized by a specific microRNAs (miRNAs) expression profile, which guides the researchers’ efforts to explore the therapeutic targets and objective biomarkers that reflect the diagnosis and disease activity in clinical use for psoriasis.The paper presents a state-of-the-art review of expression and function of miRNAs in psoriasis along with its clinical implications.We analyzed all literature searched by keywords “microRNA” and “psoriasis” in PubMed (Medline) from inception up to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 57 publications
1
87
1
Order By: Relevance
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate that aberrant epigenetic silencing of the miR-197 promoter underlies its decreased expression in psoriasis. The mechanism leading to miR-197 silencing, as well to additional alterations in miRNAs in the psoriatic lesion [25,26,50,51], should be further investigated. Study of the epigenetic structure of miR-197 and its putative promoter sequences in the psoriatic genome might partially answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that epigenetic modifications are associated with a variety of diseases, e.g. IBD78, multiple sclerosis9, psoriasis10 and systemic lupus erythematosus11. The molecular basis of epigenetic regulation is complex.…”
mentioning
confidence: 99%